Kathleen Taperell interviewed by Sara Dowse - Taperell, Kathleen (Kathleen Joan), 1939-; Dowse, Sara, 1938- (2006)
Kathleen Taperell talks about the 1993 re-election of Labor, strengthened Office of the Status of Women remained in Prime Minister & Cabinet; native title, reconciliation, Aboriginal policy branch; being head of the policy branch; women's status in public service; needing to justify function; government changes (1983) strong women's policy; taking leave without pay; the impact of illness in the family; her retirement; missing a sense of purpose, identification with job; her community service, continuing international work; report of Australian implementation of UN convention; helping to build local heritage support; chairing publications committee; her public sector achievement; specific achievements for women; public misconceptions of public sector work; valuing the public sector; changes in gender relations; promoting social harmony; opposing negative views about state power addressed; her personal style; her gratitude for stimulating work.
Recorded on October 27, 2006 at Canberra, A.C.T.
Digital master available
Interview with Kathleen Taperell, retired public servant, Head of the Office of Women's Affairs, 1977-1984, member of the UN Status of Women Commission
Kathleen Taperell was born in Sydney 1939 and educated at the University of Sydney and the University of New England. In 1990 she became a Member of the Order of Australia. Taperell had a distinguished and varied public service career for over two decades before retiring in 1995. She joined the Public Service Board 1974 and afterwards became a senior research officer for the Royal Commission on Australian Government Administration, where she co-authored a discussion paper on women in the public service.
Timed summary and corrected transcript (typescript, 26 leaves) available.
Keywords: Taperell, Kathleen -- 1939- -- Interviews; Australia. -- Office of Women's Affairs -- Officials and employees; Feminists -- Australia -- Interviews; Public officers -- Interviews; Women -- Government policy -- Australia